2005
DOI: 10.2174/1381612054864993
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Treatment in Chronic Neuropathic Pain: The Role of Antidepressants

Abstract: Antidepressant drugs have been widely used for many years to treat neuropathic pain, despite the rationale for their use was still unclear. We review recent insights into their mechanism of action, focusing on central and peripheral analgesic actions. Beside the traditional monoaminergic hypothesis, other pharmacological actions have been studied: antidepressants interfere with the opioid system, interact with the NMDA receptors, and inhibit ion channel activity. Firm evidence from randomised controlled trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 95 publications
(108 reference statements)
0
35
0
2
Order By: Relevance
“…Antidepressant drugs are efficacious and have been widely used in the management of chronic pain conditions (Max et al, 1987;Richeimer et al, 1997). Firm evidence has shown that tricyclic antidepressants (TCAs) should be considered the gold standard treatment for neuropathic pain (Coluzzi and Mattia, 2005;Sindrup et al, 2005). It has also been reported that the analgesic effect of antidepressants is independent of their antidepressive action, and occurs at lower doses and with a faster onset of action in a clinical situation (Pilowsky et al, 1982;Onghena and Van Hondenhobe, 1992;Richeimer et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressant drugs are efficacious and have been widely used in the management of chronic pain conditions (Max et al, 1987;Richeimer et al, 1997). Firm evidence has shown that tricyclic antidepressants (TCAs) should be considered the gold standard treatment for neuropathic pain (Coluzzi and Mattia, 2005;Sindrup et al, 2005). It has also been reported that the analgesic effect of antidepressants is independent of their antidepressive action, and occurs at lower doses and with a faster onset of action in a clinical situation (Pilowsky et al, 1982;Onghena and Van Hondenhobe, 1992;Richeimer et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, there were no group differences in threshold or mean pain rating, suggesting that all subjects perceived the pain to an equal extent. The absence of difference implies that medications did not affect our results even though some studies show that SSRIs and other antidepressants can increase pain tolerance (Coluzzi & Mattia, 2005).…”
Section: Discussionmentioning
confidence: 71%
“…Other possible analgesic mechanisms suggested for AMT include increase in the release of endogenous opioids, blockade of N-methyl-Daspartate (NMDA) receptors, blockade of Na + and Ntype Ca + channels and opening of K + channels. 19,20 Several mechanisms of anti-nociceptive activity of PCM have been proposed by different researchers but the exact mechanism of action still remains to be elucidated. First well known and widely accepted mechanism includes inhibition of several isoforms of cyclooxygenase (COX) enzyme.…”
Section: Discussionmentioning
confidence: 99%